Study protocol for a pilot evaluation of Talk With Me Baby (TWMB) for Well-Child Care: A primary care-integrated language promotion intervention in rural and underserved clinics - Brenda Salley; Margaret Jaynes; David Huss; Kristina Foster; DeAnn Hubberd; Kyle Pohl; Stephen Adkison; Phyllis Nader; Jaime Baldner; Melody Greer; Jing Jin; Linda Y. Fu; et al. (PLoS ONE, 2026)
A child’s home language environment (HLE) refers to the quality of early language exposure and linguistic interactions with caregivers. A robust HLE is a primary public health consideration, as it positively influences a child’s early- and long-term academic, health and economic outcomes. Talk With Me Baby for Well-Child Care (TWMB) was developed to encourage a robust HLE within routine pediatric healthcare. While this approach has been deployed in a variety of settings, TWMB has not been rigorously evaluated in rural and underserved primary care settings. This paper describes a research protocol to evaluate the preliminary efficacy of TWMB in clinics serving rural or underserved families. At least 66 child-caregiver dyads will be recruited over 5 months (child age two to six months at enrollment) from two primary care clinics. All participants will receive the TWMB intervention during routine WCC visits at participating clinics during a 12-month period. Participants will complete baseline and post-intervention assessments of their HLE. Preliminary efficacy outcomes include changes in the caregivers’ language-promotion behaviors (as measured by Language Environment Analysis normative scores for daily Conversational Turn Count between the adult and child and daily Adult Word Count) from baseline to 12 months post-intervention. This trial has been prospectively registered as NCT06479278 on 2024-06-26.